Using Social Media as a Research Tool for a Bespoke Web-Based Platform for Stakeholders of Children With Congenital Anomalies: Development Study - Marlene Sinclair; Julie E M McCullough; David Elliott; Paula Braz; Clara Cavero-Carbonell; Lesley Dornan; Anna Jamry-Dziurla; Ana João Santos; Anna Latos-Bieleńska; Ausenda Machado; Lucía Páramo-Rodríguez (JMIR Publications, 2021)
BackgroundLimited research evidence exists on the development of web-based platforms for reciprocal communication, coproduction research, and dissemination of information among parents, professionals, and researchers. This paper provides learning and the outcomes of setting up a bespoke web-based platform using social media. ObjectiveThis study aims to explore the establishment of a web-based, multicontextual research communication platform for parents and stakeholders of children with congenital anomalies using social media and to identify associated research and ethical and technical challenges. MethodsThe ConnectEpeople e-forum was developed using social media platforms with a stakeholder engagement process. A multilevel approach was implemented for reciprocal engagement between parents of children with congenital anomalies, researchers, health care professionals, and other stakeholders using private and invisible and public Facebook groups, closed Twitter groups, and YouTube. Ethical approval was obtained from Ulster University. ResultsNonprofit organizations (N=128) were invited to engage with an initial response rate of 16.4% (21/128). Of the 105 parents contacted, 32 entered the private and invisible Facebook groups to participate in the coproduction research. Public Facebook page followers rose to 215, a total of 22 posts had an engagement of >10%, and 34 posts had a reach of over 100. Webinars included requested information on childhood milestones and behavior. YouTube coverage included 106 ConnectEpeople videos with 28,708 impressions. Project information was obtained from 35 countries. The highest Facebook activity occurred during the early morning hours. Achievement of these results required dedicated time management, social media expertise, creativity, and sharing knowledge to curate valuable content. ConclusionsBuilding and maintaining a multilayered online forum for coproduction and information sharing is challenging. Technical considerations include understanding the functionality and versatility of social media metrics. Social media offers valuable, easily accessible, quantitative, and qualitative data that can drive the reciprocal process of forum development. The identification and integration of the needs of the ConnectEpeople e-forum was a key driver in the dissemination of useful, meaningful, and accessible information. The necessary dedicated administration to respond to requests and posts and collate data required significant time and effort. Participant safety, the development of trust, and the maintenance of confidentiality were major ethical considerations. Discussions on social media platforms enabled parents to support each other and their children. Social media platforms are particularly useful in identifying common family needs related to early childhood development. This research approach was challenging but resulted in valuable outputs requiring further application and testing. This may be of particular importance in response to COVID-19 or future pandemics. Incorporating flexible, adaptable social media strategies into research projects is recommended to develop effective platforms for collaborative and impactful research and dissemination.